2017
DOI: 10.1108/ebr-08-2016-0113
|View full text |Cite
|
Sign up to set email alerts
|

A mediated model of relationship quality factors affecting behavioural intention at a luxury motor vehicle dealership

Abstract: Purpose The aim of this study is to determine whether customer satisfaction, trust and commitment as relationship quality factors can be valuable to a luxury motor vehicle dealership in generating favourable behavioural intentions concerning post-purchase service and repair offerings. Design/methodology/approach A descriptive research design was followed, and self-administered questionnaires were fielded among customers of the luxury motor vehicle dealership. A total of 301 questionnaires were returned and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 77 publications
0
14
0
6
Order By: Relevance
“…Previous studies have additionally found a positive and significant relationship between trust and customer commitment within the luxury motor vehicle (Van Tonder et al, 2017), the business-to-business (Morgan & Hunt, 1994) and the hospitality industries (Li & Chang, 2016). Trust is believed to reduce perceived risk and thereby enhance a customer's commitment to the provider.…”
Section: Conceptual Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have additionally found a positive and significant relationship between trust and customer commitment within the luxury motor vehicle (Van Tonder et al, 2017), the business-to-business (Morgan & Hunt, 1994) and the hospitality industries (Li & Chang, 2016). Trust is believed to reduce perceived risk and thereby enhance a customer's commitment to the provider.…”
Section: Conceptual Modelmentioning
confidence: 97%
“…Empirical support of the interaction effects between customer satisfaction, trust, perceived value and commitment can be found in various studies. For example, the relationship between customer satisfaction and commitment has been confirmed in the luxury motor vehicle industry (Van Tonder, Petzer, & Van Zyl, 2017), as well as in media retailers and travel agencies industries (Hennig-Thurau, 2004). It is believed that customers who have experienced satisfactory performances will want to remain loyal to the organisation (Johnson, Sivadas & Garbarino, 2008, p. 355).…”
Section: Conceptual Modelmentioning
confidence: 99%
“…No mundo cada vez mais globalizado, conectado e rápido, vivendo em um ambiente de negócios altamente competitivo e com as necessidades dos clientes mudando constantemente é difícil reter clientes e muito fácil perdê-los para a concorrência, resultando em perdas financeiras para as organizações (Giovanis, Athanasopoulou, & Tsoukatos, 2015;Tonder, Petzer, & Zyl, 2017). As empresas que prestam serviços buscam implementar uma gestão focada na qualidade dos seus serviços para que potencializarem a satisfação dos seus clientes.…”
Section: Qualidade Na Prestação De Serviço (Qps)unclassified
“…A associação da qualidade dos serviços prestados na intenção de reutilização da oficina de concessionárias automotivas autorizadas Neste cenário, construir um relacionamento com os clientes de longo prazo é importante para a sobrevivência do negócio (Khojastehpour & Johns, 2014;Tonder et al, 2017). A prestação de serviço tornou-se uma parte importante na estratégia competitiva das empresas que fabricam equipamentos para indústrias manufatureiras (Guajardo, Cohen & Netessine, 2015).…”
Section: Qualidade Na Prestação De Serviço (Qps)unclassified
“…According to Van Tonder, Petzer and Van Zyl (2017), the level of competition between service organisations is increasing in South Africa and in other parts of the world, as these organisations operate in a dynamic and competitive business environment. The critical question in service innovation research is whether service innovations within service organisations differ from innovations in manufacturing organisations.…”
Section: Introductionmentioning
confidence: 99%